2015
DOI: 10.1016/j.watres.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding on agglomeration mechanisms and thermodynamic properties of TiO2 nanoparticles interacting with natural organic matter

Abstract: Interaction between engineered nanoparticles and natural organic matter is investigated by measuring the exchanged heat during binding process with isothermal titration calorimetry. TiO2 anatase nanoparticles and alginate are used as engineered nanoparticles and natural organic matter to get an insight into the thermodynamic association properties and mechanisms of adsorption and agglomeration. Changes of enthalpy, entropy and total free energy, reaction stoichiometry and affinity binding constant are determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 71 publications
2
28
0
Order By: Relevance
“…3 (a and b) indicated that the zeta potential and particle size of hematite NPs suspended in VG will be different if they are added to a VG suspension than if the VG suspension is added to hematite NPs. Such results are also found in good agreement with the findings of Loosli et al (2015). Using isothermal titration calorimetry they found that the mixing procedure between TiO 2 nanoparticles and alginate polysaccharide chains was playing key roles in the complexation mechanisms.…”
Section: Hematite Np Stability As a Function Of Vinal Gum Concentrationsupporting
confidence: 87%
“…3 (a and b) indicated that the zeta potential and particle size of hematite NPs suspended in VG will be different if they are added to a VG suspension than if the VG suspension is added to hematite NPs. Such results are also found in good agreement with the findings of Loosli et al (2015). Using isothermal titration calorimetry they found that the mixing procedure between TiO 2 nanoparticles and alginate polysaccharide chains was playing key roles in the complexation mechanisms.…”
Section: Hematite Np Stability As a Function Of Vinal Gum Concentrationsupporting
confidence: 87%
“…In order to correlate the performance of these dispersants, isothermal titration calorimetry (ITC) was used to calculate the binding constant ( K a ), enthalpy changes (Δ H ), and thermodynamic parameters for the interaction between different PAA architectures and the surface of TiO 2 particles . Importantly, comparing different polymer architectures with the same DP n eliminates molecular weight effects and allows the influence of structure on dispersant performance to be probed.…”
Section: Resultsmentioning
confidence: 99%
“…It denotes the role of van der Waals interactions (especially for Type I) and change of conformation of SRHA. Such a behavior is not observed when linear natural polysaccharide (alginate) are considered 64 . This was due to the alginate chemical properties for which van der Waals interactions are not favored.…”
Section: Effect Of Tio 2 -Srha Agglomeration and Surface Charge On Bimentioning
confidence: 94%